Like What You Like or Like What Others Like? Conformity and Peer Effects on Facebook - Johan Egebark; Mathias Ekström (Research Institute of Industrial Economics (IFN), 2011)
Users of the social networking service Facebook have the possibility to post status updates for their friends to read. In turn, friends may react to these short messages by writing comments or by pressing a Like button to show their appreciation. Making use of five Swedish accounts, we set up a natural field experiment to study whether users are more prone to Like an update if someone else has done so before. We distinguish between three different treatment conditions: (i) one unknown user Likes the update, (ii) three unknown users Like the update and (iii) one peer Likes the update. Whereas the first condition had no effect, both the second and the third increased the probability to express a positive opinion by a factor of two or more, suggesting that both number of predecessors and social proximity matters. We identify three reasonable explanations for the observed herding behavior and isolate conformity as the primary mechanism in our experiment.
Keywords: A14; C93; D03; D83; 330; Herding Behavior; Conformity; Peer Effects; Field Experiment; Herdenverhalten; Soziale Norm; Social Web; Social Web; Feldforschung; Schweden